The gender gap in lifetime earnings: A microsimulation approach - Rick Glaubitz; Astrid Harnack-Eber; Miriam Wetter (LABOUR, 2024)
To obtain a more complete understanding of the persisting gender earnings gap in Germany, this paper investigates both the cross-sectional and lifetime dimension of gender inequalities. Based on a dynamic microsimulation model, we analyse how gender differences accumulate over work lives to examine the lifetime dimension of the gender gap. We estimate an average gender gap in lifetime earnings of 51.5 per cent for birth cohorts 1964–72. We show that this unadjusted gender lifetime earnings gap increases strongly with the number of children, ranging from 17.3 per cent for childless women to 68.0 per cent for women with three or more children. Results from a counterfactual analysis approach show an adjusted gender gap in lifetime earnings of around 10 per cent, suggesting that the gender gap in lifetime earnings is rather driven by gender differences in observable characteristics than by differences in rewards.
Keywords: 380